2014
DOI: 10.3126/ije.v3i3.11063
|View full text |Cite
|
Sign up to set email alerts
|

Computational Mining of Microsatellites in the Chloroplast Genome of Ptilidium pulcherrimum, a Liverwort

Abstract: Microsatellites also known as simple sequence repeats (SSRs) are found in DNA sequences.These repeats consist of short motifs of 1-6 bp and play important role in population genetics, phylogenetics and also in the development of molecular markers. In this study chloroplastic SSRs (cpSSRs) in the chloroplast genome of Ptilidium pulcherrimum, downloaded from the National Center for Biotechnology Information (NCBI), were detected. The chloroplast genome sequence of P. pulcherrimum was mined with the help of a Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The density of cpSSRs in T. pellucida (1 SSR/3.04 kb) found to be lower than the density of cpSSRs in Anthoceros formosae (1 SSR/2.4 kb; Shanker, 2013d) and Marchantia polymorpha (1 SSR/1.83 kb; Shanker, 2014c), however, higher than the density of cpSSRs in Aneura mirabilis (1 SSR/5.68 kb; Shanker 2013e), Pellia endiviifolia (1 SSR/7.09 kb; Shanker, 2014b), and Ptilidium pulcherrimum (1 SSR/5.17 kb; Shanker, 2014a). Moreover, it is higher than the density of EST-SSRs in barley, maize, wheat, rye, sorghum and rice (1 SSR/6.0 kb; Varshney et al 2002), cpSSRs of rice (1SSR/6.5 kb; Rajendrakumar et al, 2007), Unigene sequences of Citrus (1 SSR/12.9 kb; Shanker et al, 2007a), average density of chloroplast genomes of Rosales (1 SSR/5.12 kb; Srivastava and Shanker, 2015a) and Magnoliids (1 SSR/6.91 kb; Srivastava and Shanker, 2015b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The density of cpSSRs in T. pellucida (1 SSR/3.04 kb) found to be lower than the density of cpSSRs in Anthoceros formosae (1 SSR/2.4 kb; Shanker, 2013d) and Marchantia polymorpha (1 SSR/1.83 kb; Shanker, 2014c), however, higher than the density of cpSSRs in Aneura mirabilis (1 SSR/5.68 kb; Shanker 2013e), Pellia endiviifolia (1 SSR/7.09 kb; Shanker, 2014b), and Ptilidium pulcherrimum (1 SSR/5.17 kb; Shanker, 2014a). Moreover, it is higher than the density of EST-SSRs in barley, maize, wheat, rye, sorghum and rice (1 SSR/6.0 kb; Varshney et al 2002), cpSSRs of rice (1SSR/6.5 kb; Rajendrakumar et al, 2007), Unigene sequences of Citrus (1 SSR/12.9 kb; Shanker et al, 2007a), average density of chloroplast genomes of Rosales (1 SSR/5.12 kb; Srivastava and Shanker, 2015a) and Magnoliids (1 SSR/6.91 kb; Srivastava and Shanker, 2015b).…”
Section: Resultsmentioning
confidence: 96%
“…These repeats act as molecular markers in many plant genomes and also identified in bryophytes (Shanker, 2014a;2014b;2014c;Pandey et al, 2016). However, the distribution of SSRs in chloroplast genome of Tetraphis pellucida Hedw.…”
Section: Introductionmentioning
confidence: 99%
“…1. The frequency of each SSR repeats (mono-to hexa) in four bryophytes species (Shanker 2013a(Shanker , 2013b(Shanker , 2014a(Shanker , 2014b reviewed extensively (Zane et al, 2002;Weising et al, 2005;Kalia et al, 2011). Hutsemékers et al (2008 identified 8 nuclear microsatellite loci in the aquatic moss Platyhypnidium riparioides using the microsatellite-enriched library's method.…”
Section: Development Of Microsatellite Through Genomic Library Constructionmentioning
confidence: 99%
“…Homoplasy is usually common in compound or interrupted repeats (Adams et al, 2004) and it can be categorized in two groups (a) Table 3. Total number of microsatellites identified by screening chloroplast genome sequence of bryophytes (Shanker et al, 2013a(Shanker et al, , 2013b(Shanker et al, , 2014a(Shanker et al, , 2014b detectable homoplasy, (b) non detectable homoplasy. The detectable homoplasy can be revealed by nucleotide sequencing.…”
Section: Microsatellites Points Of Issuementioning
confidence: 99%
“…Several important suggestions were made to decrease the overall consumption such as: replacing the old obsolete electric wire; integrating the regulators with the ceiling fans to adjust the load based on the ambient conditions; replacing manual switches with automated sensory switches; installing occupancy sensors etc. Shanker (2014) studied the chloroplastic simple sequence repeats (cpSSRs) found in DNA sequences. Author found cpSSRs in the chloroplast genome of Ptilidium pulcherrimum, downloaded from the National Center for Biotechnology Information (NCBI).…”
mentioning
confidence: 99%